الحمل على المعنى طريق إلى فض المشكل النحوي والدلالي - سعداني, لخضر (University of Eloued جامعة الوادي, 2015)
من أهم المشكلات التي تواجهنا في فهم بعض الاستعمالات اللغوية في النص القرآني بالخصوص، مشكلة تبدو في عدم التلاؤم بين الكلمة وما يتطابق معها نحويا أو دلاليا. وقد انتبه علماؤنا المسلمون والعرب من أهل النحو والتفسير لهذه الإشكالية النحوية الدلالية، بطرق منها "الحمل على المعنى ". وبذلك يصبح النص مفهوما، وربما مفتوحا على عدد من التأويلات. وهذا المقال يبسط الفكرة، ويؤيدها بالتطبيق على النص الكريم One of the greatest problematic is one which prevents us from understanding some linguistic uses in the holy Koran. It appears in the form of incompatibility between the used word , and with which it is related syntactically or semantically. Arab scholars, and Interpretants Muslims of the Koran, and grammarians had conscience of that problematic . In the way to resolve this state of double aspects, they devoted themselves to install a solution . It is consideration of the word meaning. By this procedure, the text of the Holy Qur'an is understood and clear, and sometimes open to many interpretations. This article attempts to detail the idea of <<considering the sense >> when it comes to fix its syntactic or semantic function in the sentence, putting the application on the Koran.
Keywords: النص القرآني، النحو، التفسير; Quranic text, grammar, interpretation